Comparison of Spouse Social Support and Spiritual Well-being in Women With Planned and Unplanned Pregnancies in Bushehr, South of Iran - Zahra Havaei; Masoomeh Kheirkhah; Shima Haghani (نشریه پرستاری ایران)
Background & Aims Pregnancy is an important event in a woman's life. Unplanned pregnancy significantly contributes to negative outcomes. Social support, particularly from the spouse, plays a vital role in preventing the negative outcomes of unplanned pregnancy. The spiritual well-being of women can help with managing stress during unplanned pregnancies. This study aims to compare the spiritual well-being and spouse social support in women with planned and unplanned pregnancies in Bushehr, South of Iran. Materials & Methods In this descriptive-comparative study, 384 pregnant women (192 with planned pregnancy and 192 with unplanned pregnancy) participated. They were selected from mothers who visited comprehensive health centers in Bushehr from May to September 2023. Data collection tools included a sociodemographic/fertility form, Yildirim's spouse social support scale (SSS), and Paloutzian and Ellison's spiritual well-being scale (SWBS). Data analysis was performed in SPSS software, version 16 using descriptive and inferential statistics. Results The mean total score of SSS was 72.26±4.92 in women with planned pregnancies and 69.93±6.56 in women with unplanned pregnancies. The SSS score and its dimensions in women with unplanned pregnancies were significantly lower than in women with planned pregnancies (P<0.001). The mean total score of SWBS was 67.9±2.89 in women with planned pregnancy and 68.12±12.68 in women with unplanned pregnancy. The SWBS score was not significantly different between the two groups (P=0.448). There was a significant correlation between the SSS and SWBS scores. The total SSS score was significantly related to religious well-being (P=0.017) and total SWBS score (P=0.037) in women with unplanned pregnancy, and the social support score of the SSS was significantly related to religious well-being (P=0.021) in women with planned pregnancy. Conclusion Increasing social support from the spouse can increase the religious and spiritual well-being of women with unplanned pregnancies. It can also increase the religious well-being of women with planned pregnancies. Trained midwives and healthcare providers can provide the couples with related education and help them adapt and enhance their spiritual well-being.